Pr??ticas pedag??gicas: ensino de hist??ria e cultura afro-brasileira nas escolas de Parna??ba-PI - Ribeiro, Irlanda Maria Silva (2018)
The study approaches the teaching of Afro-Brazilian History and Culture in the schools of the city of Parna??ba-PI. The objective of this study was to find out whether the teaching of Afro-Brazilian history and culture, in the perspective of Law 10.639 / 03, in the context of the pedagogical practices of the teachers of the History discipline of the state public schools of the city of Parna??ba-PI. the education of ethnic-racial relations. For this study we used a theoretical framework that addresses racial themes in Brazil and in school. In the investigation of the studied phenomenon was used the qualitative approach with bibliographical and empirical contribution. The procedures used to collect data were from bibliographic and field research. It was used as an instrument to collect the data, interviews with four teachers of the discipline of History of public high schools, in addition to a bibliographic research. The content analysis technique was used to cut and analyze the interviews. The results of the research revealed that the approach of the teaching of Afro-Brazilian history and culture by teachers, in the perspective of the law, in the context of the education of ethnic-racial relations, happens in a very limited way, with many interferences, fragilities and difficulties. He also demonstrated that the work towards Law 10.639 / 03 does not depend only on the doing and wanting of teachers, but on changes in the school's exclusionary structures, on new practices and pedagogical rituals that speak about the racial issue, including it in the planning, Political Pedagogical Project and school routines, teacher training, material resources, among other things.